Statistical modeling of heat transfer enhancements through controlled temperature and surface modifications: A fundamental understanding of nanofluid behavior - Ratchagaraja Dhairiyasamy; Saurav Dixit; Subhav Singh; Deepika Gabiriel (Results in Engineering)
This work investigated the impact of surface modifications on silver nanoparticles (AgNPs) dispersed in deionized water to enhance heat transfer performance. Three distinct nanofluids were prepared with AgNPs coated with citrate (Ag/C), lipoic acid (Ag/L), and silica (Ag/S) shells. A custom-built heat pipe experimental setup measured the nanofluids' thermal conductivity and heat transfer coefficients over a temperature range of 30–90 °C. The thermophysical properties, including density, specific heat, thermal conductivity, and viscosity, were systematically characterized across the temperature range. The convective heat transfer coefficients, thermal resistance, and overall heat transfer rates were evaluated and compared against deionized water as a baseline. The results demonstrated significant differences based on the surface modification type. Ag/L exhibited the highest thermal conductivity enhancement, while Ag/S demonstrated the most substantial thermal resistance reduction and increased heat transfer coefficients. Compared to deionized water, Ag/S showed a 7.41 % increase in heat transfer rate at 90 °C. The findings underscore the pivotal role of surface chemistry in dictating heat transfer characteristics and the potential of surface-modified AgNP nanofluids for efficient thermal management in applications such as electronics cooling, heat exchangers, and energy systems. Further research could explore long-term stability, synergistic effects of hybrid nanoparticles, computational modeling, scalability, and environmental implications to fully harness the remarkable potential of these advanced nanofluids.